Budget impact analysis of multiple varicella vaccination strategies: a Mexico perspective. Issue 4 (2nd April 2020) - Graham, Jonathan; Wolfson, Lara J.; Kyle, Jeffrey; Bolde-Villarreal, Carlos Perez; Guarneros-DeRegil, Diana B; Monsanto, Homero; Pillsbury, Matthew; Talbird, Sandra; Daniels, Vincent J.
ABSTRACT: A number of live-attenuated varicella vaccines are produced globally that provide protection against the varicella zoster virus. In Mexico, varicella vaccination is not included in the national immunization program and is recommended for use only in high-risk subgroups. We developed a budget impact model to estimate the impact of universal childhood immunization against varicella on the national payer system in Mexico. A scenario of no varicella vaccination was compared to scenarios with vaccination with a single dose at 13 months of age, in alignment with the existing program of immunization with the measles-mumps-rubella vaccine. Nine different vaccination scenarios were envisioned, differing by vaccine type and by coverage. Varicella cases and treatment costs of each scenario were computed in a dynamic transmission model of varicella epidemiology, calibrated to the population of Mexico. Unit costs were based on Mexico sources or were from the literature. The results indicated that each of the three vaccine types increased vaccine acquisition and administration expenditures but produced overall cost savings in each of the first 10 years of the program, due to fewer cases and reduced varicella treatment costs. A highly effective vaccine at 95% coverage produced the greatest cost savings.